Rapid review of ECG interpretation in small animal practice / Mark A. Oyama, Marc S. Kraus, Anna R. Gelzer - Oyama, Mark A.; Kraus, Marc S.; Gelzer, Anna R. (Boca Raton : CRC Press LLC, 2020)
The standard electrocardiogram (ECG) is an indispensable, safe, and inexpensive test to assess dogs and cats with heart disease. This bestselling user-friendly book discusses the principles of electrocardiography, then systematically explores the evaluation of the ECG, including determination of heart rate, measurement of intervals, derivation of mean electrical axis, and criteria for atrial/ventricular enlargement or hypertrophy. At the core of this book is an extensive series of ECG cases for the reader to work through: practice makes perfect. New to this edition: Instructions on how to obtain an ECG A new chapter on the treatment of the most common clinically important ECG arrhythmias A second new chapter on 24-hour ECG (Holter) monitoring A handy one-page reference guide of important ECG values and diagrams, which can be downloaded from the book's webpage for easy reference 15 new ECG cases have been added to the original 46 cases, with a selection of advanced cases geared toward readers craving more challenging topics such as electrical cardioversion and pacemaker function. This updated edition will further aid veterinarians in their quest to better interpret the ECG. It provides information in an appealing, accessible, and easy to use format that fits with the busy lives of veterinary practitioners
OCLC-licensed vendor bibliographic record.
Keywords: MEDICAL / Veterinary Medicine / Food Animal; Veterinary electrocardiography -- Examinations, questions, etc; Dogs -- Diseases -- Diagnosis -- Examinations, questions, etc; Cats -- Diseases -- Diagnosis -- Examinations, questions, etc